Tips dan strategi meraih kejayaan umkm dusun buntaran di era digital - syauqiyah, habibatus; nur ramadhani, adelia octavia; erbean, sherif prast; amarrudin, andika iqbal (Maliki Interdisciplinary Journal, 2025)
This article discusses strategies and tips for increasing the success of Micro, Small and Medium Enterprises (MSMEs) in Buntaran Hamlet in the digital era. With advances in technology, especially the internet, MSMEs are faced with new challenges and opportunities in running a business. Even though Buntaran Hamlet has abundant local resource potential, many MSMEs have difficulty adapting to digital technology due to limited infrastructure, especially internet access. This research uses qualitative descriptive methods, through interviews and observations to identify the challenges faced by MSME actors. The research results show that education and training, optimizing the use of simple technology, and implementing efficient digital marketing strategies are important steps to support MSMEs. Apart from that, advocacy for improving internet infrastructure and building local business community networks is also key to increasing competitiveness. By implementing these suggestions, it is hoped that MSMEs in Buntaran Hamlet can develop and contribute to the local economy.